Emotional Experiences of Pregnant and Postpartum People with Confirmed or Suspected COVID-19 Infection During the Initial Surge of the Pandemic - Natalie C. Spach; Elana F. Jaffe; Kristen A. Sullivan; Cindy Feltner; Anne D. Lyerly; Ilona T. Goldfarb (Mary Ann Liebert, 2022)
Objectives: The COVID-19 pandemic may have a unique emotional impact on pregnant people. This qualitative study aimed to characterize the emotional effects of the COVID-19 pandemic on pregnant and recently pregnant patients who had either suspected or confirmed COVID-19 infection during the initial 6 months of the pandemic. Methods: Pregnant and recently pregnant participants (n?=?20) from Massachusetts General Hospital Obstetrics and Gynecology clinical sites with suspected or confirmed COVID-19 infection were interviewed about their experiences during the COVID-19 pandemic. Interviews were transcribed and coded using NVivo 12 software. Using data display matrices, thematic analysis was performed to identify emergent, crosscutting themes. Results: Twenty pregnant and postpartum patients participated of whom 12 had confirmed COVID-19 infection and 8 had suspected infection. The most frequently described emotions were anxiety (90%), uncertainty (80%), fear (70%), relief (65%), and sadness (60%). The following three crosscutting themes were identified: risk, protection, and change. The ways in which participants articulated their emotional reactions to the themes of risk, protection, and change were complex and varied. Conclusions: There was a broad range of negative and positive emotional experiences of pregnancy, birth, and the postpartum period during the first 4 months of the COVID-19 pandemic. A better understanding of pregnant people's emotional experiences may lead to changes in clinical practice and institutional policies that are more supportive of their needs and congruent with their values.